2004
DOI: 10.1063/1.1643919
|View full text |Cite
|
Sign up to set email alerts
|

Study of kinetic shear Alfvén instability in tokamak plasmas

Abstract: Kinetic shear Alfvén modes in tokamak plasmas ͑with or without temperature gradient͒ are numerically investigated in the full gyrokinetic limit. It is shown that, in the presence of ion temperature gradient ͑ITG͒, the threshold value of plasma pressure gradient is well below that for ideal magnetohydrodynamic ballooning instability. It is also demonstrated in a more general sense that, without ITG, the former is identical with the latter. The electromagnetic instability is also found to exist in the second sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(44 citation statements)
references
References 21 publications
3
40
1
Order By: Relevance
“…Qualitatively similar results are obtained in the case with higher shear, s = 1.0: here the second MHD stable domain is also destabilized by ITG-driven αTAEs in the entire parameter range scanned. Thus, our results disagree with those presented by Dong et al [7] who observed a destabilization only near the second MHD stability boundary.…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…Qualitatively similar results are obtained in the case with higher shear, s = 1.0: here the second MHD stable domain is also destabilized by ITG-driven αTAEs in the entire parameter range scanned. Thus, our results disagree with those presented by Dong et al [7] who observed a destabilization only near the second MHD stability boundary.…”
Section: Resultscontrasting
confidence: 99%
“…Our choice of parameters allowed us to revisit two cases which were examined in earlier numerical studies of Alfvénic ITG (AITG) instabilities; one with lower magnetic shear, s = 0.4 [2], and one with higher shear, s = 1.0 [7]. The results reported by Hirose et al [2] for the case with lower shear, s = 0.4, are reproduced and we are now able to explain the observations in that and subsequent studies [2,7,3,4,5,6] in terms of ITGdriven αTAE ground states [9] and on the basis of the theoretical framework provided by the generalized fishbone-like dispersion relation (see [21] for a review). Apart from clarifying earlier results, this new interpretation has two important implications:…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The above simplified calculations also show very similar jump behavior as that by a more comprehensive 1D scanning [37] of parameters for unconventional ITGs using HD7 [38] code. Considering that to obtain the quantitative (especially the global) critical gradient is still challenging due to sensitive of numerical model as mentioned in Sec.I, those discussions are out of the scope of the present study.…”
Section: Eigenstates Jump With Velocity Space Integralsupporting
confidence: 65%
“…The most unstable solutions in the ballooning space found in the past have usually the ballooning-angle parameter ϑ k = 0 [11], which corresponds to the solution localized at the outside midplane, i.e., θ p = 0 in our notation, where θ p is defined as the local peaking poloidal angle for the mode structure. For this reason, many local eigenvalue codes such as HD7 [12] assume implicitly ϑ k = 0. The unconventional eigen modes with θ p = 0 have been recently discovered in the strong gradient parameter regime.…”
mentioning
confidence: 99%